Tanggung Jawab Negara dan Korporasi dalam Pelanggaran HAM Struktural Geotermal Pulau Flores - Bernadus Febriyanto; Hernadi Affandi (Legalita, 2026)
The Flores Geothermal Island policy, established under Minister of Energy and Mineral Resources Decree No. 2268 K/30/MEM/2017, positions the region as a strategic national energy hub but has sparked intense conflict and strong opposition in various locations such as Poco Leok, Wae Sano, and Mataloko. This study aims to analyze the systematic forms of structural Human Rights (HR) violations occurring within the geothermal energy projects and to reconstruct the roles of the state and corporations based on environmental justice principles and international HR standards. Using a normative legal research method, this study finds that the state has failed to fulfill its core obligations to respect, protect, and fulfill the basic rights of indigenous peoples. This failure is manifested in the repeated disregard for the principle of Free, Prior, and Informed Consent (FPIC), violation of the right to a healthy environment, social fragmentation of indigenous communities, and the increasing criminalization of project opponents. A transformative role reconstruction requires the holistic fulfillment of the three pillars of David Schlosberg's environmental justice recognition, procedural, and distributive justice as well as strict corporate compliance with the UN Guiding Principles on Business and Human Rights. In conclusion, the long-term sustainability of energy development in Flores can only be achieved by recognizing the sovereignty of indigenous peoples as legitimate subjects of development.